Analysis of the Role and Contribution of Coastal Women to Family Income in Talise Village, West Likupang District, North Minahasa Regency - Tambani, Grace O.; Rangan, Jety K.; Kotambunan, Olvie Vanda (Jurnal Ilmiah PLATAX, 2026)
The purpose of this study is to identify and carefully analyze the roles of coastal women and the types of independent businesses they engage in, not only as housewives but also as family economic supporters in Talise Village, West Likupang District, and to analyze the contribution of women's income to family income. This study was conducted in Talise Village, West Likupang District. The respondents used as samples in this study were married women who owned businesses, had activities outside the home, and resided in Talise Village. The sampling method used in this study was purposive sampling, a sampling technique based on certain considerations such as population characteristics or previously known characteristics (Notoatmodjo, 2010). Some of the respondent criteria were: married, owned businesses, had activities outside the home, and resided in Talise Village. The total number of respondents was 20. This research will contribute to the achievement of UNSRAT's 2021–2025 Strategic Plan for Maritime Excellence, focusing on the research topic of Empowering and Enhancing Women's Participation and Social Inclusion in the Maritime Environment. Keywords: Women's Roles and Contributions, Family Income, Talise Village Abstrak.  Tujuan penelitian ini adalah untuk mengidentifikasi dan menganalisis dengan cermat bentuk peran perempuan pesisir serta bentuk usaha mandiri, selain sebagai ibu rumah tangga, juga sebagai penyokong perekonomian keluarga di Desa Talise, Kecamatan Likupang Barat, serta menganalisis besarnya kontribusi pendapatan perempuan terhadap pendapatan keluarga. Penelitian ini dilakukan di Desa Talise, Kecamatan Likupang Barat. Responden yang  dijadikan sampel dalam penelitian ini yaitu perempuan yang sudah menikah, punya usaha, punya aktivitas di luar rumah dan bermukim di Desa Talise. Metode pengambilan sampel yang digunakan dalam penelitian ini adalah purposive sampling, yaitu teknik pengambilan sampel yang berdasarkan suatu pertimbangan tertentu seperti sifat-sifat populasi ataupun ciri-ciri yang sudah diketahui sebelumnya (Notoatmodjo, 2010)11. Beberapa kriteria responden yaitu : sudah menikah, punya usaha, dan punya aktivitas di luar rumah serta tinggal di Desa Talise. Jumlah responden berjumlah 20 orang. Penelitian ini akan berkontribusi pada pencapaian RENSTRA UNSRAT 2021 –2025 di Bidang Unggulan Kemaritiman yang difokuskan pada topik riset Pemberdayaan dan Peningkatan Partisipasi Perempuan dan Inklusi Sosial dalam Lingkungan Kemaritiman. Kata Kunci: Peran dan Kontribusi Perempuan, Pendapatan Keluarga, Desa Talise